2014
DOI: 10.1093/nar/gku1287
|View full text |Cite
|
Sign up to set email alerts
|

Synergic interplay of the La motif, RRM1 and the interdomain linker of LARP6 in the recognition of collagen mRNA expands the RNA binding repertoire of the La module

Abstract: The La-related proteins (LARPs) form a diverse group of RNA-binding proteins characterized by the possession of a composite RNA binding unit, the La module. The La module comprises two domains, the La motif (LaM) and the RRM1, which together recognize and bind to a wide array of RNA substrates. Structural information regarding the La module is at present restricted to the prototypic La protein, which acts as an RNA chaperone binding to 3′ UUUOH sequences of nascent RNA polymerase III transcripts. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(140 citation statements)
references
References 39 publications
(87 reference statements)
6
131
0
3
Order By: Relevance
“…Slf1p and Sro9p are RBPs and their LAM is required for their function, and appear to contribute to selective mRNA‐binding . However, the LAM is not able to bind RNA by itself, and additional cis ‐domains that would cooperate with the LAM in S. cerevisiae LARPs have not been detected so far . Hence, how Slf1p and Sro9p bind RNA remains a challenging enigma.…”
Section: Molecular and Physiological Roles Of The Saccharomyces Cerevmentioning
confidence: 99%
See 2 more Smart Citations
“…Slf1p and Sro9p are RBPs and their LAM is required for their function, and appear to contribute to selective mRNA‐binding . However, the LAM is not able to bind RNA by itself, and additional cis ‐domains that would cooperate with the LAM in S. cerevisiae LARPs have not been detected so far . Hence, how Slf1p and Sro9p bind RNA remains a challenging enigma.…”
Section: Molecular and Physiological Roles Of The Saccharomyces Cerevmentioning
confidence: 99%
“…26 Although absolutely necessary, the LAM is not able to bind RNA alone and cooperates with an adjacent RNA recognition motif (RRM1) and the interdomain linker to form the RNA-binding pocket known as the La-Module. [26][27][28][29] La and related proteins form a superfamily of eukaryotic factors, which classify into five clusters: the genuine La and four LARP subfamilies: LARP1, 4, 6 and 7 15 (Figure 1). Most LARPs retained a La-module organization, but unlike the LAM which diverged very little, the RRM1 and interdomain linker are specific to each subfamily.…”
Section: The La-motif and La-module (Lam-rrm1): Common Themes To Genumentioning
confidence: 99%
See 1 more Smart Citation
“…Only one endogenous ligand has been identified: in mammals, LARP6 binds to a secondary structure element in the 5′ untranslated region (5′UTR) of type I collagen mRNAs [8,9]. Recently, the high-resolution structures of the individual La motif domain and the RRM domain of human LARP6 protein were solved by solution NMR [10]. The biochemical experiments that accompanied these structures demonstrated that the interdomain linker between the La motif and the RRM plays a critical role in the RNA binding activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the high-resolution structures of the individual La motif domain and the RRM domain of human LARP6 protein were solved by solution NMR [10]. The biochemical experiments that accompanied these structures demonstrated that the interdomain linker between the La motif and the RRM plays a critical role in the RNA binding activity [10]. …”
Section: Introductionmentioning
confidence: 99%